Analisis Kepuasan Petani Terhadap Kegiatan Penyuluhan Pertanian di Kelurahan Kalampangan, Kota Palangka Raya Kalimantan Tengah - Berkat Berkat; Revi Sunaryati (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2015)
This research is aimed at to know the satisfaction of farmer about farming extesionactivities at Village Kalampangan. The data were collected 42 sample farmers through questionrurires.Then the data were analyzed by using descriptive and nonparametric statistics it's the spearman correlation. The results of research showed thatfarmer satisfaction about farming extesion activities has satisfed category. Dimensions of quality serttices that's tangible, reliability, responseiveness, assurctnce, and empatlry, was positive coruelation with farmer satisfaction at village Kalampangan, Palangko Raya city.